TINGKAT PENGANGGURAN TERBUKA MEMEDIASI DAMPAK INDEKS PEMBANGUNAN MANUSIA, PRODUK DOMESTIK REGIONAL BRUTO DAN UPAH MINIMUM KABUPATEN/KOTA TERHADAP KEMISKINAN - Encep Saefullah; Muhammad Angga Anggriawan (Universitas Bina Bangsa, 2022)
The purpose of this study is to analyze poverty and determine the impact of the Human Development Index (IPM) variable, Gross Regional Domestic Product (GRDP), Regency/City Minimum Wage (UMK) on Poverty in Banten Province with Open Unemployment Rate (TPT) as a Mediation Variable . The analytical tool used is PLS SEM analysis. Based on the analysis of the number of poor people in Banten province in 2021, it still shows a high poverty rate of 6.66%, an increase compared to the previous year. From the results of the study, it can be explained that the variables HDI (X1), GRDP (X2) and UMK (X3) have a direct impact on the Poverty variable (Y) of 99.3%, and the indirect impact on the variables HDI (X1), GRDP (X2) and UMK (X3) through TPT (Z) on the variable Poverty (Y) of 93.6%. Furthermore, the discussion is explained further in this study